New Synthetic Operon Vectors for Expressing Multiple Proteins in the Chlamydomonas reinhardtii Chloroplast - Jihye Yeon; Stephen M. Miller; Wipawee Dejtisakdi (My University, 2023)
Microalgae are a promising platform for generating valuable commercial products, including proteins that may not express well in more traditional cell culture systems. In the model green alga Chlamydomonas reinhardtii, transgenic proteins can be expressed from either the nuclear or chloroplast genome. Expression in the chloroplast has several advantages, but technology is not yet well developed for expressing multiple transgenic proteins simultaneously. Here, we developed new synthetic operon vectors to express multiple proteins from a single chloroplast transcription unit. We modified an existing chloroplast expression vector to contain intercistronic elements derived from cyanobacterial and tobacco operons and tested the ability of the resulting operon vectors to express two or three different proteins at a time. All operons containing two of the coding sequences (for C. reinhardtii FBP1 and atpB) expressed the products of those genes, but operons containing the other two coding sequences (C. reinhardtii FBA1 and the synthetic camelid antibody gene VHH) did not. These results expand the repertoire of intercistronic spacers that can function in the C. reinhardtii chloroplast, but they also suggest that some coding sequences do not function well in the context of synthetic operons in this alga.
Keywords: Chlamydomonas reinhardtii; Algal biology and biofuel production